Cooperation in Online Conversations: The Response Times as a Window Into the Cognition of Language Processing - Jacquet, Baptiste; Baratgin, Jean; Jamet, Frank (Frontiers in Psychology, 2019)
Previous research in the field of cognitive science has demonstrated the relevance of measuring delays between a stimulus and a response to describe the cognitive cost of inferring the meaning of an utterance from what has been said. Yet it has rarely been studied in the context of conversations and, to our knowledge, never in free-flowing, interactive conversations. This study presents a novel way of analyzing entire online conversations in a protocol inspired by the Turing Test, by Grice's Cooperative Principle and by Sperber and Wilson's Relevance Theory to investigate the relation between violations of Grice's Cooperative Principle, humanness and the response times of the participants in 15 minutes long free-flowing conversations. We hypothesized that response times are directly correlated to the cognitive cost required to generate implicatures from a statement. Our results are coherent with the literature in the field and shed some new light on the effect of violations on the humanness of a conversational agent. We show that violations of the maxim of Relation had a particularly important effect on response times and on the perceived humanness of a conversation partner. Violations of the first maxim of Quantity and of the fourth maxim of Manner did not have as much of an effect, and only on male participants